The status of consumer protection in Malaysia - Amin, Naemah (2015)
This paper surveys the current status of consumer protection law in Malaysia since the introduction of the CPA. Since consumer protection law covers a wide spectrum of both private and public law, the discussion only focuses on main areas of consumer interests and current issues affecting Malaysian consumers. The protection afforded by the CPA would be the central focus of the discussion and the extent to which the Act has improved the position of consumers in Malaysia for the past 15 years will be examined. All major development and amendment to the CPA will be highlighted. In addition, the rapid growth in e-commerce in recent years witnesses the emergence of a new group of consumers known as e-consumers. However a distance and complex nature of online transaction has led to some new problems and challenges pertaining to consumer protection. It thus requires specific discussion to answer the query as to whether the existing laws in Malaysia are adequate in providing protection and preserving the interests of online consumers. Other areas which have raised many consumer issues and complaints are credit transactions and the discussion on this matter focuses on the need for a comprehensive consumer credit law. A discussion on consumer protection will not be complete without reference to the issues of consumer redress mechanism via the Tribunal for Consumer Claims and other alternative mode of dispute settlements and effective enforcement of the law. The paper concludes that the existing law on consumer protection is not far behind the protection available in developed countries. However there are other aspects of consumer protection that yet to be regulated or in need of further improvement.